PTU-013 Trends in certification for gastrointestinal endoscopy and variations between trainee specialties: results from the uk jets database. (17th June 2017) - Siau, K; Anderson, J; Beales, I; Broughton, R; Feeney, M; Hawkes, N; McKaig, B; Pullan, R; Thomas-Gibson, S; Valori, R; Johnson, G; Wells, C; et al.
Abstract : Introduction: In the UK, endoscopy certification is overseen by the Joint Advisory Group (JAG). Since 2011, e-certification has been awarded for upper and lower GI endoscopy via the JAG Electronic Training System (JETS). We aimed to analyse trends in endoscopy e-certification, and assess for differences between trainees in gastroenterology (GI), surgical (GS) and non-medical endoscopists (NME). Method: We prospectively identified trainees awarded certification for gastroscopy, flexible sigmoidoscopy (FS) and colonoscopy from the JETS database. For each specialty, we collected data on lifetime procedural counts, formative assessments, and key performance indicators (KPIs) at the time of certification. Comparisons between specialties were analysed using a combination of chi 2, Mann-Whitney and median tests Results: Between June 2011-Dec 2016, 2857 applications were awarded certification. Since 2013, numbers for gastroscopy and provisional colonoscopy have reached steady state, whilst certification for sigmoidoscopy and full colonoscopy continue to increase (Figure 1). Trainees awarded certification comprised mainly of GI (53.2%), GS (28.5%) and NME (15.8%) trainees. GI trainees were awarded the greatest share of certification for each endoscopic modality, except for FS, which was mainly awarded to NME (78.3%). Median procedural numbers (p<0.001) and formative DOPS count (p<0.001) pre-certification varied for each modality in the order of NME>GI>GS. Caecal intubation rates (CIR) at full certification were similar between GI (95.6%) and GS (95.6%, p=0.81), but lower in NME (93.6%, p=0.02 vs. GS, p=0.006 vs. GI), despite no differences at provisional certification (median CIR 95.6%, p=0.32). Rates of D2 intubation (median 98.7%) varied across groups (GS>GI>NME, p=0.002). Certification awarded at first attempt were similar across specialties (mean 89.4%, p = 0.19), but varied for gastroscopy (NME 95.5%, GS 90.1%, GI 89.7%, p=0.01). Conclusion: Despite variations amongst trainee specialties, endoscopy certification is a transparent and robust benchmark for assessing competency, as evidenced by trainee KPIs. Further studies are required to study the impact of recent changes to certification, and if variations in KPIs exist following certification. Disclosure of Interest: None Declared